Perancangan Media Pembelajaran TIK Kelas XI Menggunakan Google Sites di SMA Negeri 1 Junjung Sirih - Megawati, Megawati; Efriyanti, Liza; Supriadi, Supriadi; Musril, Hari Antoni; Dewi, Sinta Maria (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This research was motivated by various problems that the authors found, such as the absence of the use of learning media using the google site. Time in learning this ICT is also very limited so that students find it difficult to understand what is explained by the teacher. Based on this background, the purpose of this research is to produce a website-based learning media using the google site for valid, practical, and effective class XI ICT subjects. The Research and Development (R&D) research method is the method used in this study, with the ADDIE version of the development model consisting of 5 steps, namely analysis, design, development, implement, and evaluation, as well as the Luther-Sutopo multimedia development model. The resulting product is a website-based learning media that is tested for validity, practicality and effectiveness. Based on the product tests that have been carried out, the authors get the results of the analysis of product validity tests with a number of 0.92 with valid criteria, the results of the practicality test with a number of 0.99 thus designing a very practical type of learning media and the results of the analysis of the effectiveness test with a number of 0.99 categories. very effective. Afterobtaining the results of the learning media test, it is hoped that this product can help students andteachers.